Cauchy problem for a system of linear inhomogeneous first-order differential equations with pulse action at fixed times and rectangular matrices in the system and impulses (Neliniini Kolyvannya, 2025)
We determine the solvability conditions and construct the general solution and the solution of the Cauchy problem for a system of linear inhomogeneous first-order differential equations with impulse action at fixed times and rectangular matrices in the system and impulses.